Genome‐wide identification of seed storage protein gene regulators in wheat through coexpression analysis. (27th October 2021) - Luo, Guangbin; Shen, Lisha; Zhao, Shancen; Li, Ruidong; Song, Yanhong; Song, Shuyi; Yu, Kang; Yang, Wenlong; Li, Xin; Sun, Jiazhu; Wang, Yanpeng; Gao, Caixia; et al.
Summary: Only a few transcriptional regulators of seed storage protein (SSP) genes have been identified in common wheat ( Triticum aestivum L.). Coexpression analysis could be an efficient approach to characterize novel transcriptional regulators at the genome‐scale considering the correlated expression between transcriptional regulators and target genes. As the A genome donor of common wheat, Triticum urartu is more suitable for coexpression analysis than common wheat considering the diploid genome and single gene copy. In this work, the transcriptome dynamics in endosperm of T. urartu throughout grain filling were revealed by RNA‐Seq analysis. In the coexpression analysis, a total of 71 transcription factors (TFs) from 23 families were found to be coexpressed with SSP genes. Among these TFs, TuNAC77 enhanced the transcription of SSP genes by binding to cis ‐elements distributed in promoters. The homolog of TuNAC77 in common wheat, TaNAC77, shared an identical function, and the total SSPs were reduced by about 24% in common wheat when TaNAC77 was knocked down. This is the first genome‐wide identification of transcriptional regulators of SSP genes in wheat, and the newly characterized transcriptional regulators will undoubtedly expand our knowledge of the transcriptional regulation of SSP synthesis. Significance Statement: This genome‐wide analysis followed by experimental validation identified novel candidate regulators of protein storage in seeds of common wheat.